Bodyweight status misperception among reproductive-aged women in primary care settings - Sahiran, Mohammad Faiz; Lee, Ping Yein; Mawardi, Maliza; Mohd Azizi, Fatin Nur Shaheera (Academy of Family Physicians of Malaysia, 2020)
Introduction: It is common, and many international and local studies confirm this, that women of reproductive age misperceive their body-weight status. This phenomenon can lead to their being less likely to adopt a healthy lifestyle which later exposes them to increased health problems and risks including those of a gynecological and obstetric nature. Generally, there have been inconsistent findings concerning the association between the self-perceived weight status and sociodemographic factors, physical activities, and previous weight loss attempts of women of reproductive age in an Asian population like Malaysia. Objective: This study aimed to determine the factors associated with body weight status misperception among reproductive-aged women at a primary care setting in Malaysia. Methods: This is a cross-sectional study conducted at Klinik Kesihatan Durian Tunggal in 2016-2017. The questionnaire included questions on the perception of weight status, sociodemographic factors, smoking status, level of physical activity, and weight loss attempts. Logistic regressions were used for statistical analysis to examine the association between body weight status misperception and related factors. Results: The study recruited 630 reproductive-aged women. The mean age and SD of the respondents was 32.7 + 8.9 years, and 84% of the respondents were Malays. More than three-quarters of the respondents (75.5%, n = 476) had received up to a secondary level of education. The majority of the respondents were in the overweight/obese group (59.4%, n = 374). The mean BMI of the respondents was 27.1 kg/m2 + 6.61. Approximately 65.4% (n = 412) of the respondents had an inactive lifestyle. However, 60% (n = 378) of the respondents reported that they had attempted to reduce their weight in the last year. A total of 141 respondents (22.4%) misperceived their weight status with 113 (80.1% ) of them underestimating their weight status. Women with primary-level education (OR: 3.545, 95% CI: 1.530-8.215, p = 0.003) and secondary-level education (OR: 1.933, 95% CI: 1.065-3.510, p = 0.030) had a greater likelihood of misperceiving their body weight status as compared to those who have a tertiary level of education. Women with no weight loss attempts were also at risk of body weight status misperception (OR: 1.850, 95% CI: 1.195, 2.865, p = 0.006). Conclusion: Bodyweight status misperception among reproductive-aged women was associated with a low level of education and with those who had made no weight loss attempts. Identifying women who are at risk of misperceiving their weight status would enable early counseling on weight management.